Progressive attenuation of visual global precedence across healthy aging and Alzheimer’s disease - Álvarez-San Millán, Andrea; Iglesias, Jaime; Gutkin, Anahí; Olivares, Ela I. (Frontiers in Aging Neuroscience, 2022)
In the perception of Navon hierarchical stimuli (e.g., large letters made up of small letters), young adults identify large letters faster than small ones (known as ‘global advantage’) and identify more slowly small letters when they form a different (or incongruent) large letter (known as ‘unidirectional global interference’). Since some global/local perceptual alterations might be occurring with aging, we investigated whether these effects vary across healthy aging and Alzheimer’s disease (AD). Here, the Navon letter task was administered to 26 healthy elderly (HE), 21 adults with mild cognitive impairment (MCI), and 26 adults with AD. The same task was administered 1 year later, and different neuropsychological variables were incorporated into the analyses. The cross-sectional study revealed no global advantage but did reveal both global and local interferences in all groups when response times were analyzed. Regarding discrimination sensitivity, HE showed unidirectional global interference, while AD displayed better discrimination of local than global letters in the incongruent condition, which denotes less interference by global distractors than by local ones. The longitudinal study revealed that 1 year later the participants with MCI showed a slowdown in inhibiting local distractors in the global task, revealing a certain bias toward focus in their attention on small stimuli. The elders with AD reflected a generalized slowing of their responses with a clear bias toward local analysis of stimuli, also suggested by their better discrimination in the incongruent local task at the second moment of assessment. Furthermore, all response timing measures in the Navon task were correlated with several neuropsychological indexes of highly sensitive neuropsychological tests, suggesting that performance in this task may also have a potential diagnostic value for differentiating typical from atypical cognitive aging. All these results support the need for a multidomain approach to define neuropsychological markers of progression toward AD, including visual perceptual organization evaluated via measures of performance quality.